Sustained Release Microspheres in Drug Delivery: Formulation Strategies, Characterization, and Therapeutic Application - Tusara Kanta Behera; Santosh Kumar Dash; Jyotirmaya Parida; Khagesh Bhoi; Lokesh Kumar Barik; Madhusudan Behera; Jitu Rout; Kandarpa Rana; Kundan Bishi (Asian Journal of Pharmaceutical Research and Development, 2026)
Sustained release microspheres have emerged as a promising and versatile drug delivery system capable of improving therapeutic efficacy, patient compliance, and overall treatment outcomes by providing controlled and prolonged drug release. These microspheres, typically composed of biodegradable and biocompatible polymers such as PLGA, PLA, chitosan, and alginate, are designed to encapsulate a wide range of drugs, including small molecules, peptides, and proteins, and release them at a predetermined rate over extended periods. Various formulation strategies such as solvent evaporation, spray drying, ionic gelation, coacervation, and advanced techniques like microfluidics have been extensively explored to optimize particle size, drug loading, and release characteristics. Comprehensive characterization of microspheres, including particle size analysis, surface morphology, encapsulation efficiency, thermal behavior, and in vitro drug release studies, plays a critical role in ensuring formulation stability and performance. Drug release from microspheres is governed by mechanisms such as diffusion, degradation, swelling, and erosion, which can be effectively, modeled using kinetic approaches like zero-order, Higuchi, and Korsmeyer peppas models. These systems have demonstrated significant potential across diverse therapeutic areas, including cancer therapy, diabetes management, cardiovascular diseases, infectious diseases, hormone delivery, vaccine delivery, and central nervous system disorders, with several formulations already approved for clinical use. Furthermore, recent advancements in targeted delivery, stimuli responsive systems, and nanostructured microspheres, along with integration of Quality by Design (QbD) and artificial intelligence approaches, have further expanded their application scope. Despite challenges such as burst release, scale-up difficulties, and regulatory considerations, sustained release microspheres continue to represent a cornerstone in modern pharmaceutics, offering innovative solutions for controlled and site-specific drug delivery.